Application of the Total Productive Maintenance to Increase the Overall Value of Equipment Effectiveness on Ventilator Machines - Hibarkah Kurnia; Andini Putri Riandani; Tri Aprianto (Jurnal Optimasi Sistem Industri, 2023)
This article has been corrected.